A Novel G542X CFTR Rat Model of Cystic Fibrosis Is Sensitive to Nonsense Mediated Decay - Sharma, Jyoti; Abbott, Joseph; Klaskala, Lauren; Zhao, Guojun; Birket, Susan E.; Rowe, Steven M. (Frontiers in Physiology, 2020)
Nonsense mutations that lead to the insertion of a premature termination codon (PTC) in the CFTR transcript affect 11% of patients with cystic fibrosis (CF) worldwide and are associated with severe disease phenotype. While CF rat models have contributed significantly to our understanding of CF disease pathogenesis, there are currently no rat models available for studying CF nonsense mutations. Here we created and characterized the first homozygous CF rat model that bears the CFTR G542X nonsense mutation in the endogenous locus using CRISPR/Cas9 gene editing. In addition to displaying severe CF manifestations and developmental defects such as reduced growth, abnormal tooth enamel, and intestinal obstruction, CFTR G542X knockin rats demonstrated an absence of CFTR function in tracheal and intestinal sections as assessed by nasal potential difference and transepithelial short-circuit current measurements. Reduced CFTR mRNA levels in the model further suggested sensitivity to nonsense-mediated decay, a pathway elicited by the presence of PTCs that degrades the PTC-bearing transcripts and thus further diminishes the level of CFTR protein. Although functional restoration of CFTR was observed in G542X rat tracheal epithelial cells in response to single readthrough agent therapy, therapeutic efficacy was not observed in G542X knockin rats in vivo, replicating recent human experience. The G542X rat model provides an invaluable tool for the identification and in vivo validation of potential therapies for CFTR nonsense mutations.